2017
DOI: 10.1007/s00253-017-8166-z
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification synergized with ANAMMOX for the anaerobic degradation of benzene: performance and microbial community structure

Abstract: To evaluate the effect of anaerobic ammonium oxidation (ANAMMOX) on benzene degradation under denitrification, a sequencing batch reactor (SBR) under denitrification synergized with ANAMMOX (SBR-DenAna) for benzene degradation was established by inoculating anaerobic ammonium-oxidizing bacteria (AnAOB) into a SBR under denitrification reactor (SBR-Den) for benzene degradation. The average rate of benzene degradation and the maximum first-order kinetic constant in SBR-DenAna were 2.34- and 1.41-fold those in SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The analyzed methods of COD, NH 4 + , and PO 4 3− in anodic and recovery chamber effluents, NO 3 − , NO 2 − , and pH, are referenced to the previous studies 28 . The detailed test method of nitrogen referenced to what Peng et al 29 . previously reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyzed methods of COD, NH 4 + , and PO 4 3− in anodic and recovery chamber effluents, NO 3 − , NO 2 − , and pH, are referenced to the previous studies 28 . The detailed test method of nitrogen referenced to what Peng et al 29 . previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…The analyzed methods of COD, NH 4 + , and PO 4 3− in anodic and recovery chamber effluents, NO 3 − , NO 2 − , and pH, are referenced to the previous studies. 28 The detailed test method of nitrogen referenced to what Peng et al 29 previously reported. The removal efficiencies of COD, NH 4 + , and PO 4 3− were calculated based on their difference between the influent and effluent concentrations in the anodic chamber.…”
Section: Calculations and Chemical Analysismentioning
confidence: 99%
“…These redox reactions were confirmed stoichiometrically, particularly in SO42‐reducing cultures, and revealed incomplete denitrification reactions in NO3‐reducing cultures. Consequently, the expected accumulation of H 2 S or NO2 in these environments may be deleterious for attenuations operating under these redox conditions, and the toxicity of these metabolites may require redress in engineered remediation programs, perhaps by the introduction of ferrous salts to react with sulfide (Firer, Friedler, & Lahav, 2008) or by coincubation with ammonium oxidizers that consume nitrite (Peng et al, 2017). Stoichiometric values of iron‐containing cultures also suggested a subset of reactions unrelated to Fe 3+ ‐reduction, suggesting that the bioavailability of the excess amorphous iron is limited and that concurrent methanogenic reactions may be taking place.…”
Section: Discussionmentioning
confidence: 99%
“…nitrite (Peng et al, 2017). Stoichiometric values of iron-containing cultures also suggested a subset of reactions unrelated to Fe 3+ -reduction, suggesting that the bioavailability of the excess amorphous iron is limited and that concurrent methanogenic reactions may be taking place.…”
Section: Research Articlementioning
confidence: 98%
“…Recently, it has been reported that denitrification synergized with anammox could accelerate the anaerobic degradation of benzene, and Rhodocyclaceae bacteria might play a role in benzene degradation (Peng et al, 2017 ). Although one possible contribution of anammox bacteria could be to remove the nitrite that accumulates as a result of denitrification, benzene and metabolic intermediates such as toluene, phenol and benzoate were found to inhibit anammox activity (Peng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%